Good, Bad, and Ugly Colonial Activities : Studying Development Across the Americas - Bruhn, Miriam (World Bank, Washington, DC, 2012)
Levels of economic development vary widely within countries in the Americas. This paper argues that part of this variation has its roots in the colonial era. Colonizers engaged in different economic activities in different regions of a country, depending on local conditions. Some activities were "bad" in the sense that they depended heavily on the exploitation of labor and created extractive institutions, while "good" activities created inclusive institutions. The authors show that areas with bad colonial activities have lower gross domestic product per capita today than areas with good colonial activities. Areas with high pre-colonial population density also do worse today. In particular, the positive effect of "good" activities goes away in areas with high pre-colonial population density. The analysis attributes this to the "ugly" fact that colonizers used the pre-colonial population as an exploitable resource. The intermediating factor between history and current development appears to be institutional differences across regions and not income inequality or the current ethnic composition of the population.